1992
DOI: 10.1002/jez.1402620409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of oviductal secretory proteins by estrogen‐treated ovariectomized gilts

Abstract: The objective of this study was to identify, characterize, and examine oviductal secretory proteins (OSP) synthesized de novo by whole oviduct (WO), ampulla (A), and isthmic (I) tissue from ovariectomized (OVX), corn oil (CO)-, estrogen (E)-, progesterone (P)-, and E + P-treated gilts. Oviducts were collected from OVX gilts after CO, E, P, or E + P treatment for 11 consecutive days and tissue was incubated with 3H-leucine (3H-leu). Rates of 3H-leu incorporation into nondialyzable macromolecules by WO explants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Glycoproteins secreted by non-ciliated cells create an intraluminal environment able to immobilise spermatozoa (Hunter, 1995), to maintain the viability and fertilizing capability of spermatozoa (Pollard et al, 1991;Suarez et al, 1991;Chian et al, 1995) and to play a supportive role in sperm/egg interactions (Geng et al, 1997;Tulsiani et al, 1997). Differences in the production of oestrus-associated glycoproteins by oestrogen have been observed in the isthmus of baboon (Verhage and Fazleabas, 1988) and pig (Buhi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoproteins secreted by non-ciliated cells create an intraluminal environment able to immobilise spermatozoa (Hunter, 1995), to maintain the viability and fertilizing capability of spermatozoa (Pollard et al, 1991;Suarez et al, 1991;Chian et al, 1995) and to play a supportive role in sperm/egg interactions (Geng et al, 1997;Tulsiani et al, 1997). Differences in the production of oestrus-associated glycoproteins by oestrogen have been observed in the isthmus of baboon (Verhage and Fazleabas, 1988) and pig (Buhi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the synthesis and secretion of oviduct-specific protein have been shown to be controlled by ovarian steroids (Erickson-Lawrence et al, 1989;Buhi et al, 1992;DeSouza and Murray, 1995).…”
mentioning
confidence: 99%
“…Estrogen treatment of ovariectomized animals can also restore oviductin production (Oliphant et al, 1984a;Buhi et al, ,1992Verhage et al, 1989Verhage et al, , 1990. The cyclical variations of oviductin synthesis and secretion in other mammals are more subtle, possibly because of the shorter duration of their ovarian cycles.…”
Section: Hormonal Control Of Oviductin Synthesismentioning
confidence: 99%
“…Indeed, while it has been clearly demonstrated that some of these oviduct-specific secretory proteins are released in response to endogenous estrogen at estrus in the mouse (Horvat et al, 1992), sheep (Sutton et al, 1986;Murray, 19931, human (Verhage et al, 1988), cow (Malayer et al, 1988;Gerena and Killian, 1990; Abe et al, 1993b), baboon (Ver- , and gilt (Buhi et al, 1989(Buhi et al, , 1990 or in ovariectomized estrogen-treated animals (Oliphant et al, 1984b;Buhi et al, ,1992Murray, 1993;) the role of steroid sex hormones in the control of the secretion (Malette et al, 1994) or mRNA expression (Donnelly et al, 1991;Arias et al, 1994) of others seems to be different. Some of these oviduct-specific secretory glycoproteins possess the interesting properties of interaction with the zona pellucida (zp) and/or perivitelline (PV) space of the oocyte during its passage through the oviduct and remain associated with the embryo until implantation.…”
mentioning
confidence: 99%
“…Mutual interactions between gametes and oviductal epithelium were studied during their co-cultivation in the medium saturated with steroid hormones (Reuter et al 1994). An increased secretion of the oviductal epithelium was observed after the administration of both estrogen and progesterone (Erickson-Lawrence et al 1989;Buhi et al 1991;Buhi et al 1992). Sensitivity of the structural components of the oviduct to ovarian steroid hormones was confirmed by several authors, such as Nozaki and Ito (1987), Elsimar and Coutinho (1988), Faussone-Pelegrini and Bani (1990), Hoshino and Kumasaka (1991).…”
mentioning
confidence: 76%